PENGARUH PEMBERIAN PUPUK ORGANIK CAIR (POC) LIMBAH TANDAN KOSONG KELAPA SAWIT (TKKS) TERHADAP PERTUMBUHAN Mucuna braceata D.C - Angga Oktavianus; Hagai Jorenta Perangin-angin; Suryadi Risky Sirait; Bayu Pratomo (Institut Teknologi Sawit Indonesia, 2022)
Effect of OPEFB POC Application on Mucuna bracteata Seedling Growth. This study aims to determine the effect of application and dose level of EFB POC on the growth of Mucuna bracteata seedlings. This research was conducted from January to March using an experimental method with a Non-Factorial Randomized Block Design (RAK) with four replications and 7 levels of POC TKKS treatment: (P0) No POC TKKS treatment, (P1) 5 ml/polybad POC TKKS, ( P2) 10 ml/polybad POC TKKS, (P3) 15 ml/polybad POC TKKS, (P4) 20ml/polybad POC TKKS, (P5) 25 ml/polybad POC TKKS, (P6) 30 ml/polybad POC TKKS. Research data were analyzed using analysis of variance (Analysis of variance) and Tuckey's advanced test at 5% level. The results showed that giving POC OPEFB to the growth of Mucuna bracteata seedlings had a significant effect on the growth of tendril length and number of leaves.